A companion to James Madison and James Monroe - Leibiger, Stuart Eric. (Malden, MA : Wiley-Blackwell, 2012)
A Companion to James Madison and James Monroe, features essays from leading academics that consider various aspects of the lives and legacies of our fourth and fifth presidents. Provides historians and students of history with a wealth of new insights into the lives and achievements of two of America's most accomplished statesmen, James Madison and James Monroe. Features 32 state-of-the field historiographic essays from leading academics that consider various aspects of the lives and legacies of our fourth and fifth presidents. Synthesizes the latest findings, and offers new insights based on original research into primary sources.>Addresses topics that readers often want to learn more about, such as Madison and slavery.
List of Illustrations -- Notes on Contributors -- Acknowledgments -- Introduction / Stuart Leibiger -- James Madison's Political Thought: The Ideas of an Acting Politician / Jack N. Rakove -- James Madison's Journey to an "Honorable and Useful Profession," 1751-1780 / Paul Douglas Newman -- James Madison, 1780-1787: Nationalism and Political Reform / Adam Tate -- James Madison and the Grand Convention: "The Great Difficulty of Representation" / Gordon Lloyd; Christopher Burkett -- James Madison and the Ratification of the Constitution: A Triumph Over Adversity / Kevin R.C. Gutzman -- James Madison in the Federalist: Elucidating "The Particular Structure of this Government" / Michael Zuckert -- James Madison, Republican Government, and the Formation of the Bill of Rights: "Bound by Every Motive of Prudence" / Alan Gibson -- James Madison in the U.S. House of Representatives, 1789-1797: America's First Congressional Floor Leader / Carey Roberts -- James Madison and the National Gazette Essays: The Birth of a Party Politician / Denver Brunsman -- James Madison, the Virginia Resolutions, and the Philosophy of Modern American Democracy / Garrett Ward Sheldon -- James Madison's Secretary of State Years, 1801-1809: Successes and Failures in Foreign Relations / Mary Hackett -- President James Madison's Domestic Policies, 1809-1817: Jeffersonian Factionalism and the Beginnings of American Nationalism / Aaron N. Coleman -- President James Madison and Foreign Affairs, 1809-1817: Years of Principle and Peril / David J. Siemers -- James Madison's Retirement, 1817-1836: Engaging the Republican Past, Present, and Future / James H. Read -- James Madison and George Washington: The Indispensable Man's Indispensable Man / Stuart Leibiger -- James Madison and Thomas Jefferson: A "Friendship Which Was for Life" / Jeffry H. Morrison -- James and Dolley Madison and the Quest for Unity / Catherine Allgor -- James Madison and Montpelier: The Rhythms of Rural Life / David B. Mattern -- James Madison and the Dilemma of American Slavery / Jeff Broadwater -- James Monroe's Political Thought: The People the Sovereigns / Arthur Scherr -- James Monroe, 1758-1783: Student and Soldier of the American Revolution / Daniel Preston -- James Monroe and the Confederation, 1781-1789: The Making of a Virginia Statesman / Robert W. Smith -- James Monroe in the 1790s: A Republican Leader / William M. Ferraro -- James Monroe as Governor of Virginia and Diplomat Abroad, 1799-1810: A Revolution of Principles and the Triumph of Pragmatism / David A. Nichols -- James Monroe as Secretary of State and Secretary of War, 1809-1817: Toward Republican Strategic Sobriety / Mackubin Thomas Owens -- James Monroe, James Madison, and the War of 1812: A Difficult Interlude / J.C.A. Stagg -- President James Monroe's Domestic Policies, 1817-1825: "To Advance the Best Interests of Our Union" / Michael J. McManus -- President James Monroe and Foreign Affairs, 1817-1825: An Enduring Legacy / Sandra Moats -- The Domestic Life of James Monroe: The Man at Home / Meghan C. Budinger -- James Monroe and Thomas Jefferson: Republican Government and the British Challenge to America, 1780-1826 / Michael Schwarz -- James Monroe and James Madison: Republican Partners / Brook Poston -- James Madison and James Monroe Historiography: A Tale of Two Divergent Bodies of Scholarship / Peter Daniel Haworth -- References.
Includes bibliographical references and index.
Print version record.
Keywords: Madison, James, -- 1751-1836.; Monroe, James, -- 1758-1831.; Madison, James, -- 1751-1836.; Monroe, James, -- 1758-1831.; Madison, James, -- 1751-1836; Monroe, James, -- 1758-1831; 1783-1865; Presidents -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- United States -- 19th Century; Politics and government; Presidents; United States -- Politics and government -- 1783-1865.; United States; Electronic books; Biography